¿HÉROES O VILLANOS?: LOS ACUERDOS DE COLABORACIÓN EMPRESARIAL Y SU INCIDENCIA SOBRE LA LIBRE COMPETENCIA - Sotomayor Flores, Miguel Eduardo (Revista de Derecho, 2019)
The vertiginous changes taking place in the industry, alongside the appearanceof a much more demanding consumer, had created the necessity for corporationsto establish alliances in order to overcome their lack on technical, financial, organizationalor structural capabilities. Most of the times, these alliances include anagreement or clause that could be deemed to be anticompetitive or signaled as aper se prohibition. Nevertheless, time has proved that these agreements are usuallyharmless and even able to be procompetitive, forcing competition agencies to bemore flexible in their analysis, avoiding ideological bias, thus promoting positivecollaborations for the market. In this article, we describe collusive behavior, specificallyon technological and retail markets, that is efficient and has positive consequences on the welfare of consumers. We intend to understand the economicreasons behind and study the foreign jurisprudence that addresses them. That onmind, we conclude that we should not only allow these type of alliances, but encouragethem through the government.
Keywords: competition; restraints; contracts; joint ventures; efficiency